Assessing the prevalence of schistosomiasis and strongyloidiasis in a tuberculosis clinic: the TB-TROPIcare study - Genovese, Camilla; Colaneri, Marta; Pagano, Simone; Schiuma, Marco; Galli, Lucia; Fama, Federico; Antinori, Spinello; Gori, Andrea; Torre, Alessandro (Frontiers in Tropical Diseases, 2024)
IntroductionIn recent years, Europe has experienced a significant flux of migrants, often hailing from regions endemic for schistosomiasis and strongyloidiasis, diseases frequently overshadowed by tuberculosis (TB) in healthcare priorities. While TB remains a prevalent concern among this population, chronic schistosomiasis and strongyloidiasis are frequently neglected. Motivated by this observation, we aimed to investigate the prevalence of schistosomiasis and strongyloidiasis in patients attending our TB outpatient clinic.MethodsWe conducted a retrospective, observational study spanning from June 2020 to January 2024, focusing on patients attending the TB outpatient clinic of Luigi Sacco Hospital of Milan, Italy. Serology tests were performed in patients with a history suggestive of exposure to either Schistosoma spp. or Strongyloides stercoralis.ResultsAmong the 228 patients included in the study, 84 (36.8%) individuals were born in Italy, one came from Spain, 80 (35.1%) from strongyloidiasis moderate or high endemic countries and 63 (27.6%) from areas endemic for schistosomiasis and strongyloidiasis. Of these patients, 160 (70.2%) were diagnosed with tuberculosis disease, while 68 (29.8%) had tuberculosis infection. The prevalence of schistosomiasis was 26.7%, while that of strongyloidiasis was 7.8%. Notably, 3 patients tested positive for both infections.ConclusionOur study highlights the often-underestimated prevalence of schistosomiasis and strongyloidiasis among migrants accessing healthcare for TB, underscoring the importance of increased awareness and targeted screening within this population.